Book Review: Pakistan’s Experience with Formal Law: An Alien Justice: Osama Siddique, Delhi: Cambridge University Press, 2014, ISBN 978-1-107-63627-9, paperback, first published 2013, pp. xvii+469. - Madsen, Stig Toft (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
No abstract